Karakteristik Pneumonia Pada Balita Di RSUD Labuang Baji Makassar Tahun 2021 - 2022 - Taula'bi, Welly Kondo Songgo; Wahyudin , Bob; Hariadi, Anisyah (Bosowa Medical Journal, 2024)
Pneumonia is an infection of the lung parenchyma that causes inflammation in the alveolus. As a result, the alveolus will be filled with fluid or pus, so that the air exchange process in the alveolus is disrupted. The purpose of this study was to determine the characteristics of pneumonia in toddler at Labuang Baji Hospital Makassar in 2021 - 2022. This study was a descriptive observational study that took secondary data from the medical record books of toddler patients with pneumonia at Labuang Baji Hospital Makassar. The population in this study were all toddler patients diagnosed with pneumonia by doctors at Labuang Baji Hospital Makassar in 2021 - 2022. The samples in this study were all toddler patients recorded in medical records diagnosed with pneumonia by doctors at Labuang Baji Hospital Makassar in 2021 - 2022 and met the sampling criteria. The results of 62 samples showed that the majority of pneumonia occurred in toddler age (0 - <12 months) (58.0%), male toddler (53.2%), toddler with normal birth weight (91.9%), toddler who were not exclusively breastfed (75.8%) and toddler with underweight (malnutrition) (53.2%). The study concluded that toddler age (0 - <12 months), male, with a history of normal birth weight, not exclusively breastfed and underweight (malnutrition) were found to have more pneumonia.